Analisis Pengaruh Harga Minyak Mentah Dunia, Harga Batubara, Harga Emas, Inflasi, dan Nilai Tukar terhadap IHSG - Mahendra Dedi Prasada; Irene Rini Demi Pangestuti (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to examine the effect of world crude oil prices, coal prices, gold prices, inflation, and the exchange rate on the IDX Composite. The sample used in this study is monthly data from the period January 2009 – December 2019 totaling 132 samples. This study uses the Autoregressive Distributed Lag model to test the long-term and short-term effects by applying the optimal lag. Before performing the Autoregressive Distributed Lag test, the Augmented Dickey Fuller Unit Root Test analysis and the Cointegration Bound Test were performed. The classical assumption test was carried out using the Breusch-Godfrey Serial Correlation LM Test and the Heteroscedasticity Test using the Breusch-Pagan-Godfrey method. Hypothesis testing is done by using the F test method, the coefficient of determination, and the T test. The results of this study are the gold price has a significant positive effect on the IDX in the short and long term, the exchange rate has a significant negative effect on the IDX in the short term and in the previous 1 month, but has no effect in the long term. World crude oil prices, coal prices, and inflation have no effect on the JCI, both in the short and long term.